Establishment of a silvopastoral system with Sambucus peruviana (Revista Sistemas de Producción Agroecológicos, 2018)
The project was developed in the municipality of Tuta, Department of Boyacá, Colombia. Ten farms were selected and each owner was given between 168 to 490 trees of Sambucus peruviana to be used as live fences or forage bank. The plants were propagated in nursery by means of stables, during 90 days, later they were transported to each selected farm, to proceed with the respective planting, which was carried out in the rainy season, for this activity holes of 30 cm in diameter with 40 cm depth were drilled; in some farms they were planted as fodder bank and in other as living fence. Once the trees were planted, height measurements were taken, observing the mortality and survival in each one of the farms during the first 60 days of planting, and the evaluation and monitoring of the height of the trees at 60 and 120 days was continued. For six months, simultaneously livestock producers in the region were trained, where the importance of silvopastoral systems was explained, these trainings favored the interest of the producers to establish the species in the region, since the best results in terms of survival and growth were observed in the farms where the producers complied with the instructions given. In addition, the established systems have served as a model for other producers to initiate the adoption process. The climatic conditions and the consumption of the tree by the animals, due to its high palatability or fence failure, were determining factors in the establishment of the silvopastoral system.
Keywords: feeding; supplementation; browse; cultivation; forage bank